Analyze of body mass index (BMI) and macronutrition needs for student age 11-13 - Fikri Pratama; Hendra Mashuri; I Komang Sukarata Adnyana; Fikri Pratama; Hendra Mashuri; I Komang Sukarata Adnyana (Pendidikan Jasmani, Kesehatan, dan Rekreasi Universitas Nahdlatul Ulama Sunan Giri, 2026)
Calculation of students' nutritional status can be done using measurement tools, namely anthropometry, assisted by body mass index (BMI) classification. The components of the body mass index consist of height and weight. This study aims to analyze the BMI and macronutrient needs of seventh grade students of MTs Kalifa Nusantara Denpasar. This study is a quantitative descriptive study using a survey method. The sample in this study were 66 seventh grade students of MTs Kalifa Nusantara Denpasar, with 24 (36%) males and 42 (64%) females. Based on the results of the study, it was found that 10 (15%) students were classified as severely underweight, 17 (26%) students were classified as mildly underweight, 24 (36%) students had an ideal BMI, 9 (14%) students were classified as mildly obese, and 6 (9%) students were categorized as severely obese. The average daily energy requirement for male is 2959,82 cal and for female 2529,38 cal. The average seventh grade students of MTs Kalifa Nusantara Denpasar have a non-ideal body mass index, because the calculation results of all categories except ideal (light thin, heavy and mild obesity, heavy) are 64%, while the ideal category is only 36%. This condition needs to be a concern, both for students personally, PE teachers, and parents, so that students are able to obtain balanced nutrition so that the ideal category is achieved.